Peptide-Based Vaccination Therapy for Rheumatic Diseases - Bin Wang; Shiju Chen; Qing Zheng; Yuan Liu; Guixiu Shi (Journal of Immunology Research)
Rheumatic diseases are extremely heterogeneous diseases with substantial risks of morbidity and mortality, and there is a pressing need in developing more safe and cost-effective treatment strategies. Peptide-based vaccination is a highly desirable strategy in treating noninfection diseases, such as cancer and autoimmune diseases, and has gained increasing attentions. This review is aimed at providing a brief overview of the recent advances in peptide-based vaccination therapy for rheumatic diseases. Tremendous efforts have been made to develop effective peptide-based vaccinations against rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), while studies in other rheumatic diseases are still limited. Peptide-based active vaccination against pathogenic cytokines such as TNF-α and interferon-α (IFN-α) is shown to be promising in treating RA or SLE. Moreover, peptide-based tolerogenic vaccinations also have encouraging results in treating RA or SLE. However, most studies available now have been mainly based on animal models, while evidence from clinical studies is still lacking. The translation of these advances from experimental studies into clinical therapy remains impeded by some obstacles such as species difference in immunity, disease heterogeneity, and lack of safe delivery carriers or adjuvants. Nevertheless, advances in high-throughput technology, bioinformatics, and nanotechnology may help overcome these impediments and facilitate the successful development of peptide-based vaccination therapy for rheumatic diseases.